White water - London, Jonathan, 1947-; Kastner, Jill (New York : Viking, 2001)
A boy learns to read the river when he goes white water rafting with his dad.
"Ages 4-8"--Dust jacket.
3.1
K-3
K-3
School Library Journal
Publisher's Weekly
Keywords: Rafting (Sports) -- Fiction; Green River (Utah) -- Fiction; Rafting (Sports) -- Fiction; Green River (Utah) -- Fiction